Awareness of Suicide Risk and Communication Between Health Care Professionals and Next‐of‐Kin of Suicides in the Month Before Suicide. Issue 4 (22nd June 2017) - Draper, Brian; Krysinska, Karolina; Snowdon, John; De Leo, Diego
Abstract : Based on psychological autopsy data, the study compared awareness of suicide risk in the deceased among next‐of‐kin (NOK) and health care professionals (HCPs), and communication between these two groups in the month before death. The NOKs had significantly more knowledge about the decedent's suicide warning signs than the HCPs (90.5% vs. 44.6%). Contact between NOK and HCP was initiated more often by the family than the HCPs (29.4% vs. 5.9%). The study found communication gaps between HCPs and NOK and stresses the need for suicide prevention strategies strengthening communication between these two groups.